2021
DOI: 10.1016/j.bbrc.2020.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Aβ42 and Aβ40 form mixed oligomers with direct molecular interactions

Abstract: HIGHLIGHTS Aβ aggregation underlies the pathogenesis of Alzheimer's disease.  Aβ has two main isoforms: Aβ42 and Aβ40.  Aβ42 is the main component in amyloid plaques, but Aβ40 is more abundant.  EPR studies show Aβ42 and Aβ40 interact with each other in oligomers.  Future studies should have a focus on Aβ composition of in vivo oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Whether A β 1–40 and A β 1-42 can co-fibrilise is still under debate, [95] found that mixing A β 1–40 and A β 1–42 leads to the generation of separate homomolecular fibrils. In contrast, studies have showed that mixing A β 1–40 and A β 1–42 leads to the formation of mixed oligomers and fibrils [29, 96]. However, it is accepted that A β 1–40 and A β 1–42 interact at the molecular level with increased levels of A β 1–40 inhibiting fibril formation and increased levels of A β 1–42 promoting aggregation [97100].…”
Section: Discussionmentioning
confidence: 99%
“…Whether A β 1–40 and A β 1-42 can co-fibrilise is still under debate, [95] found that mixing A β 1–40 and A β 1–42 leads to the generation of separate homomolecular fibrils. In contrast, studies have showed that mixing A β 1–40 and A β 1–42 leads to the formation of mixed oligomers and fibrils [29, 96]. However, it is accepted that A β 1–40 and A β 1–42 interact at the molecular level with increased levels of A β 1–40 inhibiting fibril formation and increased levels of A β 1–42 promoting aggregation [97100].…”
Section: Discussionmentioning
confidence: 99%
“…Another physical method, spin-label electron spin resonance (ESR) spectroscopy, has also been used as a spectroscopic ruler to locate the cross-β structure in inhomogeneous fibrils or oligomers and to explore the structural conversion and aggregation of proteins or peptides such as amyloid β-peptides, tau, transthyretin, and prion protein. [19][20][21][22][23][24][25][26][27][28] In this method, nitroxide spin-labels are introduced into the prion molecule, and one can measure the spin-spin interaction between two unpaired electrons at a distance within 20 Å using continuouswave ESR (CW-ESR) and 15 to 60 Å using double electron-electron resonance (DEER) ESR. 13,29,30 To investigate biomolecules with spin-labeled ESR, a nitroxide-based probe is attached through site-directed spin-labeling (SDSL) mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various hypotheses for AD progression, the amyloid hypothesis has been a long-term adherent to the AD in the impairment of neuronal and cognitive functions, due to the formation of plaque in the brain by the accumulation of Aβ fragments and aggregates [2,3]. There are two main isoforms of the Aβ species (Aβ40 and Aβ42) that are the most abundant that appear in the brain [4]. Although Aβ40 is more abundant than Aβ42 in the brain [5,6], Aβ40 is present only in a subset of amyloid plaques, while Aβ42 is the main Aβ species in amyloid plaques, suggesting that the aggregation of Aβ42 may precede that of Aβ40 [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…There are two main isoforms of the Aβ species (Aβ40 and Aβ42) that are the most abundant that appear in the brain [4]. Although Aβ40 is more abundant than Aβ42 in the brain [5,6], Aβ40 is present only in a subset of amyloid plaques, while Aβ42 is the main Aβ species in amyloid plaques, suggesting that the aggregation of Aβ42 may precede that of Aβ40 [4,7]. Although the structural difference between Aβ40 and Aβ42 is only two amino acid residues, Aβ42 exhibits a higher neurotoxicity than Aβ40 [8,9].…”
Section: Introductionmentioning
confidence: 99%